Trial of a capripoxvirus-rinderpest recombinant vaccine in African cattle. - Ngichabe, C. K. (1997)
Cattle were vaccinated with differing doses of an equal mixture of capripox-rinderpest recombinant viruses expressing either the fusion protein (F) or the haemagglutinin protein (H) of rinderpest virus. Animals vaccinated with 2 x 10(4) p.f.u. or greater of the combined viruses were completely protected against challenge, 1 month later, with both virulent rinderpest and lumpy skin disease viruses. Vaccination with any of the doses did not induce any adverse clinical response in the animals or transmission of the vaccine virus between animals. All cattle challenged 6 or 12 months after vaccination with 2 x 10(5) p.f.u. of the mixture of recombinant viruses were protected from severe rinderpest disease. Ten out of 18 were completely protected while the remaining 8 developed mild clinical signs of rinderpest. Cattle vaccinated with the recombinant vaccines after prior infection with the parental capripox virus showed more marked clinical signs of rinderpest after challenge with virulent rinderpest, but 9 out of 10 recovered, compared with 80% mortality in the unvaccinated controls.